Improvement of Banking Services Provided to Individuals and Legal Entities in Samarkand Region Based on World Experience - Abiev Davron Ilkhomovich (International Journal on Economics, Finance and Sustainable Development, 2022)
In this article, detailed information was given about banking services provided to customers in Samarkand region and the rate of their development, as well as the international experience implemented in the banking services system.